EFFECT OF RELIGIOUS DOMAIN ON HEALTHCARE SEEKING BEHAVIOR AMONG THE ADOLESCENTS IN ENUGU STATE, NIGERIA - Ugwu, Augustine C. (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2022)
Research has emphasized the relevance of good healthcare, and several variables have been identified as constraints to health-promoting behaviors. The present paper highlight the role of the religious domain on healthcare-seeking behavior among adolescents in Enugu state. Two hundred and forty-one respondents conveniently selected from different religious environments in Enugu state participated in the study. The respondents completed a self-report measure of health-seeking behavior. A cross-sectional research design was employed in the study. Data from the questionnaires were analyzed using the statistical package for social sciences (SPSS, Version 23). Linear regression was performed to determine the variation in HSB based on the religion domain. The result of the analysis revealed a statistically significant interaction between religious domain and HSB, F (1,239) = 41.38, p < 0.05. The adjusted R2 indicated that the religious domain contributed about 12.1% of the variation in HSB. The finding has implications for policymakers and healthcare providers.